2223. Effect of Direct-Acting Antivirals in Hemodialysis Patients with HCV: Real-Life Data. (26th November 2018) - Aydin, Nurten Nur; Aksoy, Firdevs; Yavuz, Ilknur; Iskender, Serap; Yildirim, Arzu Altunçekic; Yildiz, Ilknur Esen; Koksal, Iftihar
Abstract: Background: Hepatitis C virus (HCV) infection is widespread in hemodialysis patients worldwide. Studies of the effectiveness of new generation DAAs in the treatment of HCV infection in hemodialysis patients are limited.We investigated the effectiveness of DAAs in hemodialysis patients with HCV infection. Methods: Twenty-three HCV-positive treatment naïve or experienced (IFN/pegIFN±RBV) hemodialysis patients were enrolled.Three patients were excluded for not attending follow-ups regularly, and the data for 20 patients were included. Patients' demographic, virological, and genotypic characteristics, liver fibrosis status, DAAs started, and sustained virological responses at the 12th week (SVR12) were recorded. DAA regimens based on the treatments patients were using and potential drug interactions.Patients completing treatment were followed for 12 weeks for SVR. Results: The mean age of the patients was 57.8 (±10.5). Ninety percent were men; 55% were treatment-experienced and 45% were treatment naïve. Ninety percent were noncirrhotic and 10% had compensated cirrhosis. Of the treatment-experienced patients, 45.5% were nonresponder and 54.5% were relapsed (Table 1). Eighteen patients with Genotype 1b were treated with paritepravir-ritonavir-ombitasvir-dasabuvir(ProD) for 12 weeks, one patient with Genotype 4 received ProD+ribavirin for 12 weeks, and one patient with Genotype 2 received sofosbuvir+ribavirin for 24 weeks. HCVRNA was negative on the 4th week in 85% of patients, and was negative in all patients on the 12th week, apart from the patient receiving the sofosbuvir+ribavirinregimen. At the end of treatment, HCVRNA was negative in all patients, and the SVR12 rate was 100%. Patients' treatment responses were independent of previous treatments, liver fibrosis status, and hemodialysis duration. No marked side effects or complications were observed, apart from sleeplessness in one patient (Table 1). Conclusion: Our study data confirm that new generation DAAs in hemodialysis patients provide high SVR and are well tolerated, as in patients other than those with chronic kidney disease. Achieving cure in hemodialysis patients is important in terms of preventing cross-contamination and of global elimination of HCV. Disclosures: All authors: No reported disclosures.